Registration of 'ND Crown' chickpea. Issue 2 (20th April 2021) - Bandillo, Nonoy; Stefaniak, Thomas; Worral, Hannah; Mihov, Miho; Ostlie, Michael; Schatz, Blaine; Rickertsen, John; Wahlstrom, Cameron; Ramsey, Meredith; Dragseth, Kyle; Jacobs, Justin; Kalil, Audrey; et al.
Abstract: 'ND Crown' (Reg. no. CV‐342, PI 694865), a large‐seeded kabuli chickpea ( Cicer arietinum L.), was developed by the North Dakota State University Pulse Crops Breeding Program and approved for release by the North Dakota Agricultural Experiment Station. ND Crown, the first chickpea cultivar from the program, was selected specifically for adaptation to North Dakota growing conditions on the basis of its high yield potential, medium maturity, large seed size, and moderate resistance to Ascochyta blight. Based on 21 environments (location‐years) of yield trials across North Dakota and Montana, ND Crown had an average yield (2, 152 kg ha −1 ) that was similar to the commercial chickpea cultivars 'CDC Frontier' (2, 248 kg ha −1 ) and 'CDC Orion' (2, 108 kg ha −1 ) but significantly greater than 'Sierra' (1, 262 kg ha −1 ). ND Crown was moderately resistant to Ascochyta blight, with similar reaction as CDC Frontier and CDC Orion under moderate disease pressure. Under high disease pressure, ND Crown displayed significantly lower Ascochyta blight severity than CDC Frontier and CDC Orion. ND Crown exhibited an upright indeterminate growth habit and resistance to lodging. ND Crown had a greater percentage of large seeds (>8 mm) and higher 1, 000‐seed weight than CDC Frontier but was similar to CDC Orion. As a high‐yielding large‐seeded chickpea cultivar, ND Crown is a promising alternative to CDC Frontier and CDC Orion in North Dakota and nearby states. Core Ideas: Chickpea is the third most important legume crop globally in terms of production. ND Crown large‐seeded chickpea is the first kabuli chickpea cultivar released from the NDSU Pulse Breeding Program. ND Crown has high yield potential and is moderately tolerant to Ascochyta blight. ND Crown is a promising alternative to CDC Frontier and Orion in North Dakota and nearby states.